Protective impact resistant composite materials based on aluminium-silicate glass-ceramics - Savvova, O.V.; Voronov, G.K.; Babich, O.V.; Topchiy, V.L.; Fesenko, O.I.; Tymofieiev, V.D. (Functional Materials, 2019)
Protective impact-resistant composite materials have been synthesized and the perspectivity of their use as part of impact-resistant structures has been established. Were developed composite materials based on aluminium-silicate glass-ceramic materials and fillers - silicon carbide and zirconium oxide stabilized with yttrium oxide. Are established the effect of the type and content of fillers on the formation of the structure of glass-ceramic materials in correlation with their strength properties. Were obtained the samples of impact-resistant composite materials with high performance properties based on high-strength aluminium-silicate glass-ceramics in conditions of low-temperature two-stage heat treatment, which can be used as a basis for the development of protective structure elements.